2014
DOI: 10.4236/ajps.2014.53041
|View full text |Cite
|
Sign up to set email alerts
|

Use of Essential Oils of the Genus <i>Citrus</i> as Biocidal Agents

Abstract: In this study, the essential oils extracted from the peels of Citrus aurantifolia, Citrus limon and Citrus sinensis were chemically characterized and quantified. These essential oils and their standards limonene, citral and limonene + citral were evaluated (at concentrations ranging from 500 to 3.91 mL·mL −1 ) regarding their anti-trypanosome, antifungal and antibacterial activities. The chemical identification and quantification (by GC/FID and GC/MS) displayed the limonene as the major component of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
2
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
1
24
2
4
Order By: Relevance
“…The high quantity of monoterpenes followed by sesquiterpenes in the present study, with limonene as the major constituent of the C. reticulate, C. reticulata × C. sinensis , C. aurantiifolia and C. limon oils, is in agreement with data published on samples collected in other locations of Brazil for oranges (Badawy, Taktak, & El‐Aswad, ) and limes/lemons (Amorim et al, ; Gomes et al, ). The abundance of monoterpenes with limonene as the major component of Citrus oils has also been reported for samples from other countries, such as C. aurantiifolia in Vietnam (Dang et al, ), Cameroon (Tchameni et al, ), India (Fagodia, Singh, Batish, & Kohli, ) and Australia (Mirzaei‐Najafgholi, Tarighi, Golmohammadi, & Taheri, ); C. limon in India (Jain & Sharma, ) and Iran (Ghoorchibeigi et al, ); and C. reticulate in Vietnam (Dang et al, ), China (Tao, Jia, & Zhou, ), Pakistan (Zia et al, ), Nigeria (Ayoola et al, ) and Egypt (Hamdan, Mohamed, & El‐Shazly, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The high quantity of monoterpenes followed by sesquiterpenes in the present study, with limonene as the major constituent of the C. reticulate, C. reticulata × C. sinensis , C. aurantiifolia and C. limon oils, is in agreement with data published on samples collected in other locations of Brazil for oranges (Badawy, Taktak, & El‐Aswad, ) and limes/lemons (Amorim et al, ; Gomes et al, ). The abundance of monoterpenes with limonene as the major component of Citrus oils has also been reported for samples from other countries, such as C. aurantiifolia in Vietnam (Dang et al, ), Cameroon (Tchameni et al, ), India (Fagodia, Singh, Batish, & Kohli, ) and Australia (Mirzaei‐Najafgholi, Tarighi, Golmohammadi, & Taheri, ); C. limon in India (Jain & Sharma, ) and Iran (Ghoorchibeigi et al, ); and C. reticulate in Vietnam (Dang et al, ), China (Tao, Jia, & Zhou, ), Pakistan (Zia et al, ), Nigeria (Ayoola et al, ) and Egypt (Hamdan, Mohamed, & El‐Shazly, ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the yields in the present study for the mandarin/tangerine oils ( C. reticulate and C. reticulata × C. sinensis ) were higher than those reported for samples collected in Faisalabad, Pakistan, by Sadaf, Shahid, and Iqbal (), who attributed the lower yield (0.18 ± 0.03%) to the ripeness of the fruit. Gomes et al () reported higher yields that those found in the present study for C. aurantiifolia and C. limon grown in Lavras, Brazil, whereas Ghoorchibeigi, Larijani, Azar, Zare, and Mehregan, () and Tchameni, Mbiakeu, Sameza, Jazet, and Tchoumbougnang () reported lower yields than those found in the present investigation for samples of C. aurantiifolia and C. limon collected in Iran and Cameroon, respectively.…”
Section: Discussioncontrasting
confidence: 65%
“…Food poisoning outbreaks are increasingly common, so there is a need to find compounds that are able to control bacterial strains resistant to antibiotics so as to reduce the contamination and deterioration of food-products [3]. This study sought to chemically characterize the essential oils from the following medicinal plants: M. piperita, C. citratus, R. officinalis, P. boldus and F. vulgare and to evaluate their antioxidant and antibacterial activities.…”
Section: Introductionmentioning
confidence: 99%
“…Citrus essential oils are used as flavors in soft drinks, ice cream, confectionery, bakery, or as fragrances in cosmetics, perfumery, soaps and cleaning materials. Nevertheless they also have biological properties such as insecticidal and antimicrobial activity . Owing to these properties, they can be used in edible coatings for the control of postharvest diseases, increasing the shelf‐life of fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%